Modern approach to infusion therapy of pregnant women with gestational hypertension - O.V. Vaskiv; A.P. Grigorenko; O.G. Gorbatyuk; A.S. Shatkovska; A.M. Binkovska; I.A. Priymak (Medičnì Perspektivi)
To date, there are no effective treatment for placental dysfunction in pregnant women with gestational hypertension. Therefore, the purpose of our study was to investigate the clinical efficacy of proposed method of infusion therapy for pregnant women with gestational hypertension, which included a complex of drugs: pentoxifylline, arginine hydrochloride with levocarnitine and rheosorbilact. We observed 73 pregnant women with single fetation, starting from 28 weeks of gestation, who were observed before and during childbirth, and in the postpartum period by the time of discharge from the hospital. All examined women were divided into 3 groups. The first group included 30 pregnant women with gestational hypertension, who received (along with the basic therapy of methyldopa drugs) a complex of infusion solutions: pentoxifylline 0.05% – 100 ml; solution containing arginine hydrochloride 4.2% and levocarnitine 2.0% – 100 ml; reosorbilact preparation – 100 ml. The infusion was carried out once a day in the specified sequence for 10 days. The second group included 20 patients with gestational hypertension on basic therapy with methuldopa only. The control group included 23 women with physiological pregnancy. The data of our study show that in patients receiving the proposed infusion therapy there was a significant decrease in the development of placental dysfunction by 38.3%, the threat of premature birth – by 18.3% and fetal distress – by 30.0%, premature rupture of the membranes – by 35.0%, weakness of labor – by 28.3%, a decrease in the risk of perinatal central nervous system damage – by 33.3% and the frequency of cephalohematomas – by 30.0% compared with women who received only antihypertensive therapy.